Profile Optimization of Fork Head of Heavy Duty Universal Coupling based on Divide and Conquer - Liu Yuan; Yu Xiangdong; Ding Rong; He Liu (Jixie chuandong)
A profile optimization model of the fork head of universal coupling is established. Based on divide and conquer, an optimization strategy for the profile of fork head is proposed. The influence law of the six design variables on the maximum stress of the fork head is summarized. Research shows that the structural parameters of arc groove and shoulder have a significant effect on the maximum stress of fork head, which should be paid attention to in design. According to the case analysis of fork profile optimization, on the premise of keeping the rotary diameter unchanged, the maximum stress of the fork head can be reduced and the torsion transfer ability can be increased. A heavy-duty universal coupling with the largest torsion transfer capacity in China is manufactured, and the performance test is carried out, which provides a reference for the design and optimization of fork head’s profile of heavy-duty universal coupling.